2015
DOI: 10.2337/db14-0421
|View full text |Cite
|
Sign up to set email alerts
|

Blunted Brain Energy Consumption Relates to Insula Atrophy and Impaired Glucose Tolerance in Obesity

Abstract: Brain energy consumption induced by electrical stimulation increases systemic glucose tolerance in normalweight men. In obesity, fundamental reductions in brain energy levels, gray matter density, and cortical metabolism, as well as chronically impaired glucose tolerance, suggest that disturbed neuroenergetic regulation may be involved in the development of overweight and obesity. Here, we induced neuronal excitation by anodal transcranial direct current stimulation versus sham, examined cerebral energy consum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 32 publications
2
34
0
3
Order By: Relevance
“…It is not possible to confirm whether the influence of tDCS is direct/indirect or excitatory/inhibitory in the present study. Nevertheless, the repeatedly observed increased high‐energy phosphates and glucose infusion rates upon tDCS following an identical stimulation protocol indicate neuronal excitatory rather than inhibitory effects.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…It is not possible to confirm whether the influence of tDCS is direct/indirect or excitatory/inhibitory in the present study. Nevertheless, the repeatedly observed increased high‐energy phosphates and glucose infusion rates upon tDCS following an identical stimulation protocol indicate neuronal excitatory rather than inhibitory effects.…”
Section: Discussionmentioning
confidence: 96%
“…On the days of experimental testing, participants were instructed to fast for at least 16 hours. Baseline blood samples of glucose, insulin, C‐peptide, adrenocorticotrophic hormone (ACTH) and cortisol were taken, followed by a standard hyperinsulinaemic‐euglycaemic glucose clamp procedure to investigate systemic glucose tolerance as described previously . After a euglycaemic plateau in the range 4.5‐5.5 mmol L −1 had been reached, baseline blood samples were taken and the first 31 P magnetic resonance spectra were recorded.…”
Section: Methodsmentioning
confidence: 99%
“…Because only steady-state levels of glucose were measured, it is not possible to know if the differences resulted from decreased transport of glucose across the BBB or increased rates of glucose utilization. However, given the large body of evidence that obesity is associated with relative cerebral hypometabolism (18,19,28), increased cerebral glucose utilization among obese and T2DM individuals appears unlikely, thus suggesting decreases in transport activity are driving the observed changes.…”
Section: Discussionmentioning
confidence: 99%
“…Our finding in ACC differs from the results of previous studies in obesity, which mostly found a correlation of carbohydrate intake with changes in the insula. [40,41] A previous study of anorexia nervosa patients also revealed that GMV alterations in the ACC likely represent the pathophysiology underlying the dysregulation of food intake. [42] The decelerated loss of GMV has been found to be associated with intensive glycemic treatment in diabetes.…”
Section: Discussionmentioning
confidence: 99%